QUANTUM STATISTICAL PERSPECTIVE TO EXAMINE THE SOURCE CHAOS FRACTION THROUGH BOSON FEMTOSCOPY - Bary, G. (World Scientific, 2022)
Bose-Einstein correlations of identical particles reveal the shape and size of the particle emitting source of the given boson. These correlations are pivotal for a better understanding of the source dynamics and developing techniques to examine the propagation of quantum chaos in the presence of coherence at a certain temperature and momentum. Femtoscopy is of the utmost importance during this transformation for data processing and coherence-chaos analysis discrepancies. We introduced an evolving source to describe chaotic information inside quantum entanglement and the impact of the coherence order is discussed in this research. We also investigate the role of source size parameter and particle number in the dynamics of the temperature profiles with the function of momentum variation. The influences of the modeling factors on the correlations with their normalized correlator in the perspective of source coherence have been evaluated and the orientation of the source has an effect on the diffusivity of the fluid under consideration. Such consequences can cause an increase or decrease the genuine correlations due to the distributions of velocity and temperature. The main findings of the paper have been illustrated using the graphical representations of the considered correlations according to the geometry of the expanding source. Such results reveal the lucrativeness in the field of engineering applications. Â© The Author(s).